Screening of potential efficacy of dietary ginger on ethanol induced oxidative stress in rat cardiac tissue: A study on changes in basic metabolic profiles (International Journal of Pharmacy and Life Sciences, 2013)
The present study was premeditated to examine the possible mechanisms where by ginger (Zingiber officinale) could protect cardiac tissue from alcohol toxicity in rats. The carbohydrate metabolic profiles like total carbohydrates, pyruvate, total proteins, free amino acids and lactate levels were measured in heart tissue. The total carbohydrates, pyruvate, and total proteins were significant declined while free amino acids, lactate levels were significant increased in alcohol intoxicated rats. Whereas with ginger (200 mg/kg body weight) treatment shown significant increase in the total carbohydrates, total proteins and pyruvate levels, whereas free amino acids, lactate levels were significant drop in the cardiac tissues. From the present study, we conclude that ginger protects the heart tissue from alcohol toxicity in rats, this may be due to the presence of many bioactive compounds in ginger.